Working in violence: moral narratives of paramilitaries in Colombia - Manrique Rueda, Gabriela (Theoretical criminology, 2020)
This article reflects on the morality of violence workers through an analysis of the narratives of 12 former low-ranking men of the paramilitary group Heroes of Montes de Maria in Colombia. By exploring their physical and social experiences in the space of the group, and the meaning given to their actions, I argue that violence should be considered dirty work in which members construct moral representations to deal with the illegality of the group. Despite the immorality of violent actions against civilians, whose bodies were dismembered and buried in mass graves, the paramilitaries represented their mission as necessary dirty work enabling the state to guarantee civilians’ security, and creating moral obligations toward their fellows, families and communities.